Implementation of Community Participation in Environmental Protection Based on Law Number 32 of 2009 Case Study: Neighborhood Association (RT) 08, Community Association (RW) 04, Malaka Jaya, East Jakarta - Taufiq Supriadi; Dewi Dewi; Meivina Jayanti; Yong Hwa Lee (Jurnal Hukum Replik, 2026)
Environmental protection is not only the government's responsibility, but the community must also be actively involved. And environmental damage is now a very crucial problem that shows the gap between the law in the text (law in the books) and the law in practice (law in action). Law Number 32 of 2009 concerning Environmental Protection and Management provides a clear scope for the community to participate in maintaining environmental sustainability, especially starting from the micro-level community. This study aims to analyze how local community participation in implementing environmental protection in RT 08 RW 04 Malaka Jaya, East Jakarta and find solutions to avoid problems and obstacles that arise. The method used is empirical juridical legal research with a qualitative descriptive approach and data collected through direct interviews with RT/RW administrators and residents, through observation of environmental conditions, and literature studies on laws and regulations and related literature. This study has shown that the community has been involved in environmental cleaning activities. The results show that residents of RT 08 RW 04 participate through regular and active initiatives that have transformed the environment into a good example. This participation emerged from strong local awareness and broad-minded, forward-thinking leadership. It's not just a formal legal obligation, but also a challenge in addressing the consistency of participation and the varying levels of awareness. This research concludes that effective community participation can create "living law," meaning environmental norms are internalized and implemented collectively beyond the boundaries of positive law. This success has proven that even the smallest communities can be a driving force for sustainable environmental protection